A behavioural study on consumer adoption of self-collection service for e-commerce freight delivery (forced adoption) - Thum, Jie Heng (2018)
This study focuses on consumers belonging to the forced adoption stage, known as forced adopters. Forced adoption is where the consumer had to use APLs involuntarily. We will be applying the Diffusion of Innovation Theory to survey and analyze the force adopters’ intention to continue using APLs voluntarily. Through multiple regression, we found that relative advantage and compatibility were significant in determining intention to continue using APLs voluntarily, while trialability, observability and complexity were insignificant. For relative advantage, logistics players can increase the price of home deliveries, to have a wider differential in cost between home delivery and APLs. Consumers will then be able to discern the cost advantage that APLs have over home delivery and be more likely to switch to APLs. As for compatibility, logistics players can place their APLs at major transportation nodes such as train stations. Therefore, consumers can collect their parcels on the way home from work instead of making an additional trip to self-collect their parcels, making it more compatible with their lifestyle. Interviews were also conducted with logistics players to find out the advantages that APLs can bring to them, and the challenges that they face when trying to implement or use them. With perspectives from both consumers and logistics players, we can recommend research- backed strategies to increase the voluntary adoption rate of APLs among forced adopters. More consumers switching to APLs will lead to a reduction in demand for home deliveries, thereby curbing the above mentioned negative effects of the e-commerce boom.